Correlation between dental caries experience and the level of Streptococcus mutans and lactobacilli in saliva and carious teeth in a Yemeni adult population - Sounah, Sabah A.; Madfa, Ahmed A. (BioMed Central (BMC), Springer Nature, 2020)
Objective This study aimed to determine the relative amounts of Streptococcus mutans (SM) and lactobacilli (LBs) and their relationship with dental caries among a Yemeni adult population. Results A positive correlation appeared between SM and LB counts from saliva and caries tissue samples and the decayed, missing and filled teeth (DMFT) score (p?<?0.05). There was a significant correlation between SM and LBs in caries tissue (p?<?0.05). However, there was no significant difference between SM and LBs isolated from saliva samples (p?>?0.05). The number of SM and LBs in subjects with active caries was significantly higher than that in those without active caries (p?<?0.05). There was no significant difference between the daily habits and SM and LB or DMFT scores (p?>?0.05), except for a significant difference between brushing frequency and DMFT score (p?<?0.05).